PENGARUH ORIENTASI BUKAAN DAN KONFIGURASI SPASIAL TERHADAP KETERBACAAN VISUAL MEDIA PEMBELAJARAN DI RUANG KELAS : STUDI TENTANG ILUMINANSI VERTIKAL DAN DISTRIBUSI CAHAYA - Zakia Haura Lutfiyyatul Farhah; Dewi Larasati; Hanson E Kusuma; Surjamanto Wonorahardjo (Universitas Muhammadiyah Jakarta, 2026)
Classroom plays a critical role in determining the visual legibility of instructional media, directly influencing students’ comfort, concentration, and learning outcomes. Inadequate lighting design, particularly in relation to window orientation and spatial configuration, can cause glare, uneven illuminance, and poor contrast, thereby impairing the readability of both blackboards and projection screens. This study maps how established theories of visual comfort are perceived by students as classroom users under real conditions. A mixed-methods design was employed, beginning with an exploratory qualitative phase to identify students’ perceptions of ideal classroom lighting, followed by a quantitative survey analyzed using multivariate correlation techniques. Data were collected from 135 student respondents across various educational levels. The results indicate that glare from windows shows a strong positive correlation (r = 0.612) with visibility disturbance, while window orientation exhibits a moderate positive correlation (r = 0.386–0.462) with visual clarity of learning media. The accuracy of luminaire placement (r = 0.447–0.483), lamp intensity (r = 0.344–0.367), and lamp color temperature (r = 0.345–0.399) show moderate correlations with visual clarity. In contrast, the number of windows and the adequacy of daylight show weaker correlations (r < 0.300) with visual clarity variables. These findings indicate that glare control, window orientation, and the configuration of artificial lighting have a more dominant influence from the students’ perspective.